Tổng hợp và nghiên cứu phức chất của một số phối tử vòng lớn kiểu bazơ Schiff trên cơ sở thiosemicacbazit. Phần I. Các thiosemicacbazon bốn càng của glyoxal, diaxetyl, benzil và phức chất của chúng với Ni(II) và Pd(II). - Thắng, Phạm Chiến; Hải, Nguyên Minh; Độ, Vũ Đặng (Vietnam Journal of Chemistry, 2012)
The synthesis of complexes of some macrocyclic Schiff - base ligands derived from thiosemicarbazide is described. Complexes have been characterized by metal analysis and spectroscopic studies (IR, Raman, UV-Vis, 1HNMR and MS). In Ni(II) and Pd(II) complexes with bisthiosemicarbazone ligands (GBTS, ABTS, BzBTS), metal ion is tetracoordinated by four donor atoms (SNNS) from ligands to form a planar tricyclic ligating system.